Application of novel feed additives based on botanical extracts to improve productivity and economics in aquaculture - Coutteau, Peter (Avances en Nutrición Acuicola, 2010)
Citarasu, T., V. Sivaram, G. Immanuel, N. Rout and V. Murugan, 2006. Influence of selected Indian immunostimulant herbs against White Spot Syndrome Virus (WSSV) infection in black tiger shrimp, Penaeus monodon with reference to haematological, biochemical and immunological changes. Fish Shellfish Immunol., 21: 372-384. Coutteau, P., Thinh, N.H., Eskinazi, S. and H.D. Nguyen, 2010. Botanical extracts enhance disease resistance and reduce parasitic infestation in Pangasius catfish. Aquaculture Asia Pacific Magazine, Volume 6 (Number 7): 18-20. Pachanawan, A., P. Phumkhachorn and P. Rattanachaikunsopon, 2008. Potential of Psidium guajava supplemented fish diets in controlling Aeromonas hydrophila infection in tilapia (Oreochromis niloticus). J. Biosci. Bioeng., 106: 419-424. Seung-Cheol J., Takaoka, O., Jeong, G.S., Lee, S.W., Ishimaru, K., Seoka, M. And K. Takii. 2007. Dietary medicinal herbs improve growth and some non-specific immunity of red sea bream Pagrus major. Fisheries Science, 73: 63–69. Vaca, A., Cuéllar-Anjel, J., Chamorro, R., Dager, S., Coutteau, P., 2010. Panama Demo Shows Botanical Extracts Improve Shrimp Productivity. Global Aquaculture Advocate, Volume 13 (E3): 70-73. Windisch, K. Schedle, C. Plitzner and A. Kroismayr. 2008. Use of phytogenic products